2006
DOI: 10.1099/vir.0.81670-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene-expression profiles by oligonucleotide microarray in children with influenza

Abstract: In order to clarify the mechanism of the host response to influenza virus, gene-expression profiles of peripheral blood obtained from paediatric patients with influenza were investigated by oligonucleotide microarray. In the acute phase of influenza, 200 genes were upregulated and 20 genes were downregulated compared with their expression in the convalescent phase. Interferon-regulated genes, such as interferon-induced protein with tetratricopeptide repeats 2 (IFIT2) and vipirin, were strongly upregulated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…Microarray Proteomics J Proteomics Bioinform ISSN:0974-276X JPB, an open access journal neurological complications [40]. Similar microarray based studies in ferrets showed that H5N1 infection induced severe disease that was associated with strong expression of interferon response genes including the interferon-γ-induced cytokine CXCL10.…”
Section: Study Of Host Cellular Responses To Influenza a Infection Ussupporting
confidence: 50%
“…Microarray Proteomics J Proteomics Bioinform ISSN:0974-276X JPB, an open access journal neurological complications [40]. Similar microarray based studies in ferrets showed that H5N1 infection induced severe disease that was associated with strong expression of interferon response genes including the interferon-γ-induced cytokine CXCL10.…”
Section: Study Of Host Cellular Responses To Influenza a Infection Ussupporting
confidence: 50%
“…One potential explanation of the difference between evolution and adjustment rates is that highly expressed influenza genes adjust rapidly since the virus highjacks the host translation machinery. However, while a number of studies have examined expression patterns of hosts genes [36], very little is known about expression patterns of viral genes during the course of an infection. Further research in viral transcriptomics is therefore warranted.…”
Section: Resultsmentioning
confidence: 99%
“…69). Notably, as the majority of adults are herpesvirus carriers, it is conceivable that following periods of viral latency subsequent activation and replication of the virus, triggered by periods of immunosuppression, stress, trauma, or indeed other common viral infections known to raise IFN-␣ levels such as influenza (70), disease activity may be initiated in periodontitis-susceptible individuals.…”
Section: Discussionmentioning
confidence: 99%